ESTIMASI STOK KARBON DAN SERAPAN CO2 DI AREA REVEGETASI PIT MANGKALAPI PT ARUTMIN INDONESIA TAMBANG BATULICIN - Mega Aulia Rahmayanti; Ahmad Jauhari; Adistina Fitriani (Jurnal Sylva Scienteae, 2021)
This research aims to analyze land cover based on the NDVI value in the revegetation area of the 2016 planting year, estimate the carbon stock in the Falcataria moluccana stands, lower plants and brown waste as well as the CO2 absorption in the stands and make correlation between NDVI values and CO2 absorption. This research used a combination method of Vegetation Index and Ground-base Inventory. NDVI analysis on Sentinel-2 imagery was used to determine the land cover class which was then used as the basis for determining the location of the sample plot (stratified random sampling) and in the field measurements of tree diameter and height were carried out on a sample plot measuring 25 meters × 40 meters. NDVI results for the 2016 planting year of 44,51 hectare showed that there were 8 types of land cover, which were dominated by old secondary forest (NDVI value 0,60 – 0,70) covering 28 hectare and medium secondary forest (NDVI value 0,50 – 0,60) covering an area of 11,7 hectare. Average of the estimated carbon stock per hectare is 9,74 tonnes/hectare. Average of the estimated CO2 absorption is 29,93 tonnes/hectare. Based on the results of the correlation analysis, the NDVI value has a strong and positive correlation to CO2 absorption, namely 93,34% and the non-linear regression equation is y = 0.0003e17.7588x with the coefficient of determination R² = 0,8867 so that the NDVI value can be used as a basis for estimating carbon stock and CO2 absorptionPenelitian ini bertujuan untuk menganalisis tutupan lahan berdasarkan nilai NDVI di area revegetasi tahun tanam 2016, mengestimasi stok karbon pada tegakan sengon laut (Falcataria moluccana), tumbuhan bawah dan seresah serta serapan CO2 pada tegakan sengon laut dan mengetahui hubungan antara nilai NDVI dengan serapan CO2. Metode yang digunakan pada penelitian ini yaitu perpaduan indeks kehijauan dengan pengukuran lapangan. Analisis NDVI pada citra Sentinel-2 digunakan untuk menentukan kelas tutupan lahan yang kemudian dijadikan dasar untuk penentuan lokasi plot sampel (stratified random sampling) dan dilapangan dilakukan pengukuran diameter dan tinggi pohon pada plot sampel berukuran 25 meter × 40 meter. Hasil NDVI pada areal seluas 44,51 ha menunjukkan terdapat 8 tipe tutupan lahan, yang didominasi oleh hutan sekunder tua (nilai NDVI 0,60 – 0,70) seluas 28 ha dan hutan sekunder sedang (nilai NDVI 0,50 – 0,60) seluas 11,7 ha. Estimasi rata-rata stok karbon per hektare di area revegetasi pit mangkalapi adalah sebesar 9,74 ton/ha. Estimasi rata-rata serapan CO2 per hektare di area revegetasi pit Mangkalapi adalah sebesar 29,93 ton/ha. Berdasarkan hasil analisis korelasi, nilai NDVI memiliki korelasi yang kuat dan positif terhadap serapan CO2 yaitu 93,34% dan persamaan regresi non linier adalah y = 0,0003e17.7588x dengan koefisien determinasinya R² = 0.8867 sehingga nilai NDVI dapat dijadikan dasar untuk mengestimasi stok karbon dan serapan CO2